Production of Polysaccharides (Xanthan gum) by Xanthomonas campestris pv. Sesame - El Hadi, Mohamed A.; E. Ibrahim, Abdulla; M. Suliman, Hager M.; M. Abdel-Rahim, Awad; A. Abdalla, Mai (Gezira Journal of Engineering and Applied Sciences, 2018)
Many microorganisms and plants were found produce polysaccharides which are widely varying in their composition and structure. The extracellular polysaccharide produced by   Xanthomonas campestris pv. campestris , is chemically analyzed and used industrially. However, only the xanthan gum which was ranking as the best among the ten polysaccharides was used commercially in large amounts. The xanthan gum has numerous applications in food and other industries. The present study was aiming to investigate the capacity of X; campestris pv. sesami for the production of xanthan gum, using culture media containing different carbon sources. The properties of the produced material were investigated (pH, viscosity, and chromatographic analysis using thin layer chromatography).  The results showed that the weight of the product was increasing with time reaching about 9.8g at the tenth day compared to only 2.1g on the second day. The results of the effect of different carbon sources indicated that sucrose was the best giving 9.0 g in the 7 th day compared to only 1.5g by raffinose. The pH was changing from 6.7 at the beginning of the experiment to 4.2 in the tenth day. However, the viscosity of the inoculated sucrose medium was found to increase from 2.4 unit at the second day to 9.7 units after ten days. Analysis on paper chromatography showed that the produced polysaccharide contains mannose, glucuronic acid, glucose, rhamnose but no ribose nor trehalose or fructose were detected. The results indicated that the investigated bacterium was producing large amounts of xanthan gum. Although, Xanthan gum was discovered in 1950s its substantial commercial production began in 1964 and in 1969, the USA, Food and Drug Administration authorized its use in food. Xanthan gum, now has numerous uses in food and other industries. Further studies should be carried on other isolates  of the bacterium    X. campestris pv. sesami and more chemical analysis are needed.